Current perceptions and decisions of patients about cryopreserved embryos in Argentina - Natacha Salomé Lima; Constanza Branzini; Stella Lancuba (Revista de la Facultad de Ciencias Médicas de Córdoba, 2019)
Introduction: Worldwide there is an increase in the number of assisted reproduction treatments. The developments in culture media and drugs, associated with the occurrence of rapid freezing or vitrification techniques has improved the procedures encouraging transfers of a single embryo per cycle. This generates a greater number of viable surplus embryos. Embryo disposition decision making is a complex phenomenon. Method: This descriptive exploratory study investigates the perceptions and opinions of a sample of 59 participants who have started an assisted reproduction treatment in a specialized Fertility Center of the City of Buenos Aires. Results: The absence of children in the majority of the sample (70.6% still have no children) makes the prevailing option to “continue cryopreservation” (35.6%). The majority, 40.7% (24 people) consider that the option that best represents the embryo is "a child". Although there are relatively few people who have decided to donate their embryos (5 participants) several study participants report having reflected on it (43%). The vast majority (86.5%) of respondents would not be willing to face the costs of maintaining long-term cryopreservation. Conclusion: After more than three decades of assisted reproduction, Argentinean patients still face high degree of uncertainty regarding what to do with the surplus embryos. Knowing more in depth the decision-making process can help to implement communication strategies